The expanding spectrum of antibody-mediated rejection: should we include cases where no anti-HLA donor-specific antibody is detected? - Randhawa,P; Roufosse,C (American Journal of Transplantation, 2019)
Antibody-mediated rejection (ABMR) in a renal transplant biopsy is most often diagnosed by a combination of microvascular injury (MVI), C4d deposition and presence of circulating DSA. MVI designates the leucocyte margination reaction in glomeruli (glomerulitis, Banff score g) and in peritubular capillaries (peritubular capillaritis, Banff score ptc). MVI (sum of Banff scores g+ptc) is a morphological feature rather than a diagnosis, and is not specific for ABMR.